Establishing and Delivering Quality Radiation Therapy in Resource-Constrained Settings: The Story of Botswana - Efstathiou, Jason A. (J Clin Oncol, 2016)
There is a global cancer crisis, and it is disproportionately affecting resource-constrained settings, especially in low- and middle-income countries (LMICs). Radiotherapy is a critical and cost-effective component of a comprehensive cancer control plan that offers the potential for cure, control, and palliation of disease in greater than 50% of patients with cancer. Globally, LMICs do not have adequate access to quality radiation therapy and this gap is particularly pronounced in sub-Saharan Africa. Although there are numerous challenges in implementing a radiation therapy program in a low-resource setting, providing more equitable global access to radiotherapy is a responsibility and investment worth prioritizing. We outline a systems approach and a series of key questions to direct strategy toward establishing quality radiation services in LMICs, and highlight the story of private-public investment in Botswana from the late 1990s to the present. After assessing the need and defining the value of radiation, we explore core investments required, barriers that need to be overcome, and assets that can be leveraged to establish a radiation program. Considerations addressed include infrastructure; machine choice; quality assurance and patient safety; acquisition, development, and retention of human capital; governmental engagement; public–private partnerships; international collaborations; and the need to critically evaluate the program to foster further growth and sustainability.